2017
DOI: 10.21873/anticanres.11552
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Different Cancer Stem Cell Phenotypes in Breast Cancer

Abstract: Abstract. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…The findings also excluded the possibility that CXCR2 could be used as a marker of CSC in non-TNBC, because CSC is considered to be a small subpopulation of cells within the tissue, typically ≤1%. 27 …”
Section: Resultsmentioning
confidence: 99%
“…The findings also excluded the possibility that CXCR2 could be used as a marker of CSC in non-TNBC, because CSC is considered to be a small subpopulation of cells within the tissue, typically ≤1%. 27 …”
Section: Resultsmentioning
confidence: 99%
“…Cancer stem cells (CSCs) have been demonstrated to play a critical role in the initiation of metastasis, while other studies have suggested that ALDH-positive cells exhibit stem cell-like properties, thus indicating a potential role in metastatic cascade (19)(20)(21). Also, it has been reported that both CD44 + /CD24and ALDH1 + breast cancer stem cells are enriched in TNBC and may contribute to chemotherapy resistance and tumor metastasis of TNBC (22,23). Interestingly, our previous work in glioblastoma (GBM) has suggested that ALDH1A3 and CD44 expression are correlated with the aggressive and radioresistant mesenchymal (MES) subtype as compared to the proneural (PN) subtype (24).…”
Section: Introductionmentioning
confidence: 99%
“…These are related to a small fraction of stem-like cells termed as cancer stem cells (CSCs) or tumour-initiating cells (TICs) that exhibit an aggressive phenotype [1]. Breast cancer stem cells (BCSCs) have been isolated from breast cancer cell lines and breast samples from cancer patients based on a CD44 high/+ CD24 low/− phenotype and/or high ALDH (aldehyde dehydrogenase) activity [2,3]. BCSCs play an essential role in tumorigenicity as well as local invasion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…CD44 is responsible for control of numerous cellular functions, including cell adhesion, migration, homing, and transmission of growth signals [4,5,9]. Recent findings have shown that about 70% of breast cancer patients with early bone metastasis have tumours enriched in the CD44 + phenotype [3]. However, CD24 is poorly expressed in various cancer types and it is involved in cell adhesion and metastasis.…”
Section: Introductionmentioning
confidence: 99%